2021
DOI: 10.2147/opth.s298007
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Precision of Ray Tracing IOL Calculations Based on OCT Data versus Traditional IOL Calculation Formulas Based on Reflectometry in Patients with a History of Laser Vision Correction for Myopia

Abstract: Purpose To compare the refractive predictability of ray tracing IOL calculations based on OCT data versus traditional IOL calculation formulas based on reflectometry in patients with a history of previous myopic laser vision correction (LVC). Patients and Methods This was a prospective interventional single-arm study of IOL calculations for cataract and refractive lens exchange (RLE) patients with a history of myopic LVC. Preoperative biometric data were collected using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 47 publications
2
12
1
1
Order By: Relevance
“…A direct comparison of the same eyes (paired samples) would have been of interest. The reported results of Anterion-based OKULIX were comparable to results of IOL calculation studies on eyes without prior surgery 23 , 25 , 30 , 31 . In the larger cohort, Casia-based OKULIX and Barrett True-K NH both showed similar outcomes, and the Haigis-L formula achieved fewer eyes within an absPE of 0.50 dpt ( Table 1 and 2 ) 30 .…”
Section: Methods For Intraocular Lens Power Calculation In Eyes With ...supporting
confidence: 71%
See 2 more Smart Citations
“…A direct comparison of the same eyes (paired samples) would have been of interest. The reported results of Anterion-based OKULIX were comparable to results of IOL calculation studies on eyes without prior surgery 23 , 25 , 30 , 31 . In the larger cohort, Casia-based OKULIX and Barrett True-K NH both showed similar outcomes, and the Haigis-L formula achieved fewer eyes within an absPE of 0.50 dpt ( Table 1 and 2 ) 30 .…”
Section: Methods For Intraocular Lens Power Calculation In Eyes With ...supporting
confidence: 71%
“…The reported results of Anterion-based OKULIX were comparable to results of IOL calculation studies on eyes without prior surgery 23 , 25 , 30 , 31 . In the larger cohort, Casia-based OKULIX and Barrett True-K NH both showed similar outcomes, and the Haigis-L formula achieved fewer eyes within an absPE of 0.50 dpt ( Table 1 and 2 ) 30 . There are very few other studies on raytracing in eyes after LVC.…”
Section: Methods For Intraocular Lens Power Calculation In Eyes With ...supporting
confidence: 71%
See 1 more Smart Citation
“…6,8 Recently, Gjerdrum et al reported similar results using Okulix software with AS-OCT measurements by the Anterion (Heidelberg Engineering GmbH) and optical biometry by the Lenstar (Haag-Streit, Switzerland); the mean PE in their series (À0.13 D) is close to the mean PE obtained with the polynomial AL adjustment for the Holladay 2 formula (0.08 D) and the percentage of eyes with a PE within ±0.50 D was even higher (88%). 9 However, their results cannot be directly compared with this study results because they calculated the MedAE after zeroing out the mean PE and the mean AL in their series (25.3 ± 1.2) was much lower than the mean AL in this study (27.79 ± 1.97 mm). A comparison with studies evaluating traditional formulas in postmyopic refractive surgery eyes reveals that the outcomes of our study are more accurate than those obtained with any history or no-history method.…”
Section: Discussioncontrasting
confidence: 54%
“…In addition, the Scheimpflug/Placido imaging system represented by Sirius and Pentacam AXL has clinical advantages and is widely used. As for IOL calculation, despite the theoretical formulas are commonly used in calculations of IOL power, the accuracy of the ray-tracing technique has been reported previously [ 11 ]. It remains unknown whether the new apparatus and technology are affected by ICL implantation.…”
Section: Introductionmentioning
confidence: 99%